Tradução, equivalência cultural e validacão do questionário Munich Dysphagia test - Parkinson Disease (MDT-PD) para o português brasileiro - Almeida, Luciana Escanoela Zanato [UNIFESP] (2019)
Objective: to translate and validate the Brazilian version of the protocol The MunichDysphagiatest and Parkinson'sDisease (MDT-PD) Methods: A total of 102 individuals with Parkinson's disease and 95 elderly individuals who were the control group were evaluated. The objective of this study was to evaluate the Brazilian version of the Munich Dysphagia test and Parkinson's disease (MDT-PD) protocol. The translation and adaptation were performed according to the criteria of the Scientific Advisory Committee of the Medical Outcomes Trust following the steps: 1- Language and cultural translation and adaptation; 2-Validity of construct and criterion; 3-Reliability; 4- Sensitivity. Results: At the stage of translation and cultural equivalence, there were no intercurrences in the translation process, nor the need to withdraw any question, arriving at the Brazilian Portuguese version titled Dysphagia Test of Munich (TDM-DP), which presents 26 questions, in the same way as the original instrument. Regarding the validation steps, of the psychometric measures, it was possible to validate the construct, since the instrument was able to detect statistically significant differences in the self-assessment. In addition, it was possible to verify by means of regression models that there was a significant positive relation of the TDM-DP test with other instruments already validated for Brazilian Portuguese, confirming the validation of criterion. Regarding the reliability, it was possible to verify that all the questions were positively correlated. The Cronbach's alpha of 0.91 indicated that the assumption of internal consistency of the questionnaire was adequate. It was observed that the value of the intraclass correlation coefficient between the test and retest moments showed a satisfactory agreement for the complete group (r = 0.680), with respect to the sensitivity there was a difference between the pre- and post-intervention moments, with a significant reduction of the score of TDM after the intervention (p = 0.008). Conclusion: The instrument showed to have the psychometric properties necessary for the screening of the risk of dysphagia for patients with Parkinson's disease, being validated for Brazilian Portuguese with the name "Munich Dysphagia Test - Parkinson's Disease (TDM-DP)".